ANALISIS YURIDIS TERHADAP EKSEKUSI BENDA JAMINAN YANG DIBEBANI HAK TANGGUNGAN PADA DEBITUR PAILIT - SALAWATI SUYITNO (PREMISE LAW JURNAL, 2017)
Banking credit contract is generally made with hypothecation as a guarantee for paying off a debtor’s debt when he is not able to pay off his credit is declared bankrupt by the court’s ruling which is final and conclusive, and the creditor as the holder of hypothecation certificate gets legal protection. The research used judicial normative and descriptive analytic method. The research result shows that the regulation on the execution of collateral when a debtor is declared bankrupt by the court’s ruling. Procedure of the implementation of executing the collateral is that creditor as the holder of hypothecation certificate has the right to execute the collateral as if there were no bankruptcy, but the creditor has a stay period of 90 (ninety) days to do the execution. After that, he he can do the execution on his own right as if there were no bankruptcy. Keywords: Execution, Collateral, Bankrupt Debtor